Prevalence, predictors, and consequences of workplace violence among female healthcare workers in tertiary care hospitals: a cross-sectional study in Pakistan - Qurat Ul Ain Muhammad; Muhammad Ibrahim; Fazal, Faizan; Hadia Eiman; Alishba Shezal; Saeed Lehrasab (Journal of the Pakistan Medical Association, 2024)
Objective: To determine the prevalence, predictors and perpetrators of violence, and its impact on the mental health of female healthcare workers. Method: The cross-sectional study was conducted from June to October 2022 at three tertiary care hospitals after approval from the ethics review board of Rawalpindi Medical University, Rawalpindi, Pakistan, and comprised female healthcare workers, including doctors, nurses and paramedical staff. Data was collected regarding workplace violence using a structured questionnaire adopted from literature. The incidence of verbal, physical and sexual violence in the preceding 12 months was noted, and predictors were analysed. Data was analysed using SPSS 25. Results: Of the 140 subjects with an age range of 16-60 years, verbal violence was experienced by 102(72.9%) and physical violence by 26(18.6%), while verbal and physical forms of sexual violence were reported by 33(23.6%) and 13(9.3%), respectively. Those in the Medicine department had significantly lower odds of experiencing verbal violence compared to those from the Surgery department (adjusted odds ratio=0.223; 95% confidence interval: 0.078-0.036; p=0.005). Those in the Emergency department had significantly greater odds of experiencing physical violence compared to those in Surgery (adjusted odds ratio=8.716; 95% confidence interval: 1.693-44.87; p=0.01). Violence had a significant detrimental impact on the mental health of female healthcare workers (p<0.05). Conclusion: Violence was found to be prevalent in the healthcare sector, specifically in stressful and critical-care departments, like Emergency and Surgery. Key Words: Workplace violence, D064450P, Female healthcare workers, Sexual harassment, D017406, Physical violence, D000066550.